Elucidating The In Vitro Antiproliferative Properties And Associated Mechanisms Of Momordica Cochinchinensis Spreng (Gac Fruit) Aqueous Extract Using Colorectal Cancer Origin Cell Lines - Thavamany, Priscilla Jayanthi (2024)
Momordica cochinchinensis S., also known as gac fruit, is a tropical fruit native to Southeast Asia. However, it has not yet been fully explored in Malaysia. The extracts obtained were aril water extract (AW), pulp water extract (PW) and seed extracts (SW), and its ethanolic counterpart, namely aril extract (AE), pulp extract (PE) and seed extract (SE). The focus of this study in terms of their phytochemical composition, antioxidant, antimicrobial, antiproliferative, and wound healing properties. Both water and ethanolic extracts of the aril, pulp and seed contain alkaloids, flavonoids, saponins, volatile oil and reducing sugars. However, glycosides were only present in water extracts (AW, PW, SW), meanwhile tannins were detected only in SW. The PW exhibited an increased level of total phenolic content (TPC); 0.0215 ± 0.00060 mg GAE/g whereas, total flavonoid content (TFC) was quantitated at 0.083 ± 0.022 mg QE/g FW (TFC), respectively. Apart from that, the PW extract also exhibited potent antibacterial activity, with MIC values between 5 and 20 mg/ml and MBC values between 10 and 20 mg/ml against E. coli, P. aeruginosa, S. flexneri, and B. cereus. The concentrations ranged between 1μg/ml and 10 μg/ml of PE and SW extracts showed positive effects in the wound healing experiment. The aril of the fruit is known for its high concentration of carotenoids, such as beta-carotene and lycopene. These compounds are powerful antioxidants and have been shown to have an anti-proliferative effect on various types of cancer-causing cells.